2015
DOI: 10.1111/flan.12126
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Vocabulary Knowledge in German Textbooks

Abstract: Previous research on second language vocabulary acquisition has shown that learning to use a new word is not a simple matter of making a form–meaning connection. Knowing a word instead requires mastery of as many as nine different aspects of vocabulary knowledge (Nation, 2001). The current study uses data from five beginning‐level textbooks of German as a foreign language that are widely used at American universities to examine which of these aspects of vocabulary knowledge are addressed in textbook activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Pedagogically, the findings of this study suggest that while it is important for learners to develop an understanding of basic meanings for a large number of words, it is also important for them to build and consolidate a network of how the meanings of those words are related and organized in the mental lexicon. However, some analyses of L2 textbooks, albeit not Chinese ones, revealed that the two aspects of vocabulary knowledge that received the most attention were often word forms and meanings (for establishing form‐meaning connections) with little coverage of critical aspects of vocabulary depth like associations (Brown, ; Neary‐Sundquist, ). While the vocabulary focus of Chinese textbooks is unknown, there have been constant reports that Chinese learners, even advanced ones, tend to show a lack of fine‐grained understandings of word meanings, such as nuanced meanings of synonyms and their distinct collocation patterns (e.g., / [deepen or promote (understanding) vs. / [improve or broaden (knowledge)]; e.g., Li, ; Xing, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogically, the findings of this study suggest that while it is important for learners to develop an understanding of basic meanings for a large number of words, it is also important for them to build and consolidate a network of how the meanings of those words are related and organized in the mental lexicon. However, some analyses of L2 textbooks, albeit not Chinese ones, revealed that the two aspects of vocabulary knowledge that received the most attention were often word forms and meanings (for establishing form‐meaning connections) with little coverage of critical aspects of vocabulary depth like associations (Brown, ; Neary‐Sundquist, ). While the vocabulary focus of Chinese textbooks is unknown, there have been constant reports that Chinese learners, even advanced ones, tend to show a lack of fine‐grained understandings of word meanings, such as nuanced meanings of synonyms and their distinct collocation patterns (e.g., / [deepen or promote (understanding) vs. / [improve or broaden (knowledge)]; e.g., Li, ; Xing, ).…”
Section: Discussionmentioning
confidence: 99%
“…This ability requires not only knowing several words but also knowing each one of them deeply enough to be able to discern morphological commonalities and to use those as retrieval cues (Nation, ). Analyses of L2 textbooks (Brown, ; Neary‐Sundquist, ) have consistently demonstrated that the aspect of vocabulary knowledge that is emphasized the most is the meaning‐form link whereas most other aspects, such as word associations (i.e., how different words are associated) or word parts (i.e., how words are composed of smaller meaningful units—morphemes), are simply ignored or forgotten. This situation may play a role in the obtained results, and it may well be that more systematic integration of these concepts into instruction as well as more systematic training in those forgotten abilities could be beneficial in helping learners to perform better in this type of high‐complexity MA task.…”
Section: Discussionmentioning
confidence: 99%
“…Because textbooks often exert powerful authority over instructional design and practice, it is perhaps not surprising that research on L2 vocabulary learning has taken a keen interest in how textbooks present vocabulary and allow learners to practice it. Reflecting advances in corpus‐based linguistics, recent studies have critically examined commonly used L2 textbooks in terms of the distribution of high vs. low frequency vocabulary (Godev, 2009; Lipinski, 2010; Miller, 2011; Sánchez‐Gutiérrez et al, 2019), frequency of lexical input and recycling of vocabulary (López‐Jiménez, 2014), and different types of vocabulary learning activities (Brown, 2011; López‐Jiménez, 2009, 2014; Neary‐Sundquist, 2015). Much of this work has pointed to inconsistencies between the way vocabulary is treated in textbooks and recommendations informed by the research.…”
Section: Perceptions Of Vocabulary Learning and Instructional Materialsmentioning
confidence: 99%
“…Nation's (2001) taxonomy of lexical knowledge has been widely influential not only in designing materials but also for their evaluation, with two recent studies, Brown (2011) and Neary‐Sundquist (2015), applying the framework to critical analyses of L2 textbooks as the main instructional materials used in language instruction. Nation's typology includes nine aspects of vocabulary knowledge across three main categories: (1) form : spoken, written, word parts, (2) meaning : form and meaning, concepts and referents, associations, and (3) use : grammatical functions, collocations, and constraints on use.…”
Section: Perceptions Of Vocabulary Learning and Instructional Materialsmentioning
confidence: 99%